Section 235 of the constitution: Too soon or too late for cultural self-determination in South Africa? - de Villiers, Bertus (Juta and Company Ltd, 2014)
© 2014, Juta and Co ltd. All rights reserved. Section 235 of the Constitution acknowledges the right of cultural groups to selfdetermination. Giving practical effect to s 235 is a task to be undertaken by a future Parliament. This article explores the concept of non-territorial, also called cultural autonomy, whereby culture groups can establish a legal person clothed with public law powers as an organ of government to make decisions about the protection and promotion of their culture, language and customs. Several case studies where cultural autonomy is applied are referred to and recommendations are made for future consideration in South Africa.